Mobile dental clinic revitalization to improve oral health services in the covid-19 pandemic era at Sambirejo District Community Health Center, Kabupaten Langkat - Farahanny, Wandania; Andryas , Ika; Octavia N, Rini; Hanafiah, Olivia A (Talenta Publisher, 2020)
One of pandemic effect is that people being afraid to have their regular dental treatment and tends to have their own medication. Dentist and dental nurses as workerin public health provider also afraid on doing dental treatment on a reason highly contamination and transmission of the virus. Delaying aerosol generating procedures is found as the only choice, except for emergency case. However, the uncertainty of pandemic era and dental treatment needs, urge the health workers to have innovation in dental treatment service. Â Using mobile dental clinic Dinas Kesehatan Kabupaten Langkat di Puskesmas Sambirejo is a solution. The implementation of service activities in mobile dental clinic are mainly in self Protection equipment, SOP inÂ Standart Precaution, sterlisation and aseption and also patients admision flow in pandemic era for health care providers as a way to improve their knowledge in handling patient in pandemic era. The delay of action in dental procedur can be solved by facilitating mobile dental clinic according to standard health protocol. Instead of only reaching rural area, this mobile dental clinic can also be used in narrow building with limited space. The SOP protocol can also be used by dentis and dental nurses to control infection in mobile dental clinic. This article tries to support government in raising the degree of mouth and dental health services in pandemic era.